HYPERHOMOCYSTEINEMIA IN CIRRHOSIS OF THE LIVER - Juraev Bobur Rakhmonovich, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:Numerous  clinical  and  epidemiological  studies  have  identified elevated  plasma  homocysteine  levels  as  a  risk  factor  for  atherosclerotic  vascular diseases and thromboembolism. Hyperhomocysteinemia may develop due to defects in genes that metabolize homocysteine; dietary conditions that lead to a deficiency of vitamins  B6,  B12,  or  folic  acid;  or  chronic  alcohol  use.  Homocysteine  is  an intermediate  product  of  methionine  metabolism,  which  occurs  mainly  in  the  liver. Impaired  liver  function  leads  to  changes  in  the  metabolism  of  methionine  and homocysteine; however, the molecular basis of such changes is not fully understood. In addition, the mechanisms of cellular toxicity caused by homocysteineare not fully defined.